IDNStudy.com, kung saan nagtatagpo ang mga tanong at sagot. Alamin ang mga detalyadong sagot mula sa mga bihasang miyembro ng aming komunidad na sumasaklaw sa iba't ibang paksa para sa lahat ng iyong pangangailangan.

give the 5 example of equation in math


Sagot :

Answer:

Different Types of Equations

Quadratic Equation.

Linear Equation.

Radical Equation.

Exponential Equation.

Rational Equation.

Answer:

Different Types of Equations

Some of the lists of math equations involved in algebra are

  • Quadratic Equation
  • Linear Equation
  • Radical Equation
  • Exponential Equation
  • Rational Equation

Each term involved in the linear equation is either a constant or single variable or a product of a constant. The general form of linear equations with two variables is given by

Y = mx + c ,m≠0

Where m is the slope

C is the point on which it cut y-axis

Example : Linear equation with one variable : 10x – 80 = 0

Linear equations with two variables : 9x + 6y – 82 =0

Quadratic Equations

The quadratic equation is a second-order equation in which any one of the variable contains an exponent of 2. The general form of the quadratic equation is

ax2+bx+c = 0, a≠0

Example : 5x2 – 5y -35=0

Here a = 5, b=-5 and c=-35

Radical Equations

In a radical equation, a variable is lying inside a square root symbol or you can say that the maximum exponent on a variable is ½

Example : a−−√+10=26

Exponential Equations

In this math equations, it contains the variables in place of exponents. By using the property, an exponential equation can be solved. ax=ay⇒x=y

Example : 8x = 32

The above equation is equivalent to 8x = 84.

Rational Equations

A rational math equations involves the rational expressions

Example : y2=y+24

Math Equations Example

Math Equations ExampleQuestion 1 :

Find the solution for the given equation and check the answer

4x – 7 (2-x) = 3x + 2

Solution :

Given : 4x – 7 (2-x) = 3x + 2

Simplify the left side of equation within the bracket

4x – 14 + 7x = 3x + 2

11x – 14 = 3x + 2

Now, bring all the ‘x’ terms on one side and constant term on other side

11x-3x = 14 + 2

8x = 16

X = 16/8

X = 2

Therefore, the solution for the given equation 4x – 7 (2-x) = 3x + 2 is 2

Verification :

Substitute x = 2 in the equation.

4x – 7 (2-x) = 3x + 2

4(2) – 7 (2-2) = 3(2) + 2

8 – 7(0) = 6 + 2

8 = 8

Step-by-step explanation:

Correct me if im wrong

#CARRY ON LEARNING